Multi-omic profiling reveals widespread dysregulation of innate immunity and hematopoiesis in COVID-19 - Wilk, Aaron J; Lee, Madeline J; Wei, Bei; Parks, Benjamin; Pi, Ruoxi; Martínez-Colón, Giovanny J; Ranganath, Thanmayi; Zhao, Nancy Q; Taylor, Shalina; Becker, Winston; Jimenez-Morales, David; Blomkalns, Andra L; et al. (The Journal of experimental medicine, 2021)
Our understanding of protective versus pathological immune responses to SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), is limited by inadequate profiling of patients at the extremes of the disease severity spectrum. Here, we performed multi-omic single-cell immune profiling of 64 COVID-19 patients across the full range of disease severity, from outpatients with mild disease to fatal cases. Our transcriptomic, epigenomic, and proteomic analyses revealed widespread dysfunction of peripheral innate immunity in severe and fatal COVID-19, including prominent hyperactivation signatures in neutrophils and NK cells. We also identified chromatin accessibility changes at NF-κB binding sites within cytokine gene loci as a potential mechanism for the striking lack of pro-inflammatory cytokine production observed in monocytes in severe and fatal COVID-19. We further demonstrated that emergency myelopoiesis is a prominent feature of fatal COVID-19. Collectively, our results reveal disease severity-associated immune phenotypes in COVID-19 and identify pathogenesis-associated pathways that are potential targets for therapeutic intervention.